Cisplatin treatment modulates Annexin A1 and inhibitor of differentiation to DNA 1 expression in cervical cancer cells - Prates, Janesly [UNESP]; Moreli, Jusciéle Brogin; Gimenes, Alexandre Dantas; Biselli, Joice Matos [UNESP]; Pires D'Avila, Solange Correa Garcia; Sandri, Silvana; Farsky, Sandra Helena Poliselli; Rodrigues-Lisoni, Flávia Cristina [UNESP]; Oliani, Sonia Maria [UNESP] (Elsevier, 2020)
Cisplatin (Cis) is a choice chemotherapy approach to cervical cancer by inducing DNA adducts and subsequent apoptosis. We have investigated the effects of Cis on Annexin A1 (ANXA1) and inhibitor of DNA binding 1 (ID1) proteins expression to elucidate further mechanisms of Cis actions. Human cervical tissue samples from twenty-four patients, with Cervical Intraepithelial Neoplasia (CIN, stage I, II and III), were evaluated to quantified ANXA1 and ID1 expressions. In vitro, human epidermoid carcinoma of the cervix (SiHa cell line) were treated with Annexin A1 peptide (ANXA12−26), Cis or Cis + ANXA12−26 to evaluate cell proliferation and migration, cytotoxicity of treatments as well as ANXA1 and ID1 modulations by mRNA and protein expression. Our findings showed expression of ID1 and ANXA1 proteins in tissue samples from Cervical Intraepithelial Neoplasia (CIN) patients, with intense immunological identification of ID1 in the CIN III stage. In SiHa cells, treatments with Cis alone or Cis + ANXA12−26, increase mRNA expressions of the ANXA1 and reduced the ID1. In agreement, Cis + ANXA12−26 enhanced ANXA1 protein expression and Cis or Cis + ANXA12−26 abolished ID1 protein expression. Cell proliferation was reduced after treatment with ANXA12−26 peptide and more significant after Cis or Cis + ANXA12−26 treatments. These two last treatments reduced cell viability, by inducing late apoptosis, and impaired cell migration. Together, our data highlight endogenous ANXA1 is involved in Cis therapy for cervical cancer.
Keywords: Apoptosis; Cell proliferation; Gene expression; Peptide ANXA12-26; SiHa cells